2020
DOI: 10.3390/vaccines9010005
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Biomarkers of Oxidative Stress in Cattle Vaccinated with Tick Recombinant Antigens: A Pilot Study

Abstract: Tick vaccination is an environmentally friendly alternative for tick control, pathogen infection, and transmission. Tick vaccine protection is sometimes incomplete, which may be due to problems in the stability, conformation, and activity of antibodies. This might be related to oxidative stress, but more studies are needed about the possible relationships between oxidative stress and immune function. The objective of this study was to evaluate and compare various serum biomarkers of antioxidant response and ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
2
6
1
Order By: Relevance
“…The latter may be attributed to the antioxidant effect of Vit E/Se administration in the vaccinated ewes of group VE. Accordingly, the total antioxidant capacity was found to be decreased in cattle 28 days after vaccination with tick recombinant antigens [16]. However, in the present study, on day 21, the TAC levels were normalized among the groups, which may be related to the different vaccines used and the fact that the time of delivery was approaching.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The latter may be attributed to the antioxidant effect of Vit E/Se administration in the vaccinated ewes of group VE. Accordingly, the total antioxidant capacity was found to be decreased in cattle 28 days after vaccination with tick recombinant antigens [16]. However, in the present study, on day 21, the TAC levels were normalized among the groups, which may be related to the different vaccines used and the fact that the time of delivery was approaching.…”
Section: Discussioncontrasting
confidence: 69%
“…The redox status during the immune response could be affected by various factors, i.e., species, age, microbial agent, and active or passive route. In a recent study conducted by Contreras et al [16], no lipid peroxidation was found during the active immunization, something that could be assumed for the interpretation of the TBARS results of the present study. The TBARS showed a significant decline 12 h after the treatment within both the VE and V groups.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A significant decrease in oxidizing markers was observed, with the exception of thiol. The authors concluded that those vaccines that are capable of inducing lower oxidative stress allow the production of higher levels of antibodies [67]. In our study, we observed a high level of FRAP in the group after vaccination 2, which was related to the fact that all people had a positive response and a correspondingly high level of antibodies.…”
Section: Discussionsupporting
confidence: 55%
“…Fourth, normal concentration of uric acid has antioxidant capacity. 19–21 In this study, the level of uric acid in the AAE group was significantly lower than that in the control group. It is suggested that increasing uric acid may play a certain protective effect on the occurrence of AAE in patients with CKD.…”
Section: Discussionmentioning
confidence: 45%